How Hospitable Are Space Weather Affected Habitable Zones? The Role of Ion Escape - Airapetian, Vladimir S.; Glocer, Alex; Khazanov, George V.; Loyd, R. O. P.; France, Kevin; Sojka, Jan; Danchi, William C.; Liemohn, Michael W. (Astrophysical journal. Letters, 2017)
Atmospheres of exoplanets in the habitable zones around active young G-K-M stars are subject to extreme X-ray and EUV (XUV) fluxes from their host stars that can initiate atmospheric erosion. Atmospheric loss affects exoplanetary habitability in terms of surface water inventory, atmospheric pressure, the efficiency of greenhouse warming, and the dosage of the UV surface irradiation. Thermal escape models suggest that exoplanetary atmospheres around active K-M stars should undergo massive hydrogen escape, while heavier species including oxygen will accumulate forming an oxidizing atmosphere. Here, we show that non-thermal oxygen ion escape could be as important as thermal, hydrodynamic H escape in removing the constituents of water from exoplanetary atmospheres under supersolar XUV irradiation. Our models suggest that the atmospheres of a significant fraction of Earth-like exoplanets around M dwarfs and active K stars exposed to high XUV fluxes will incur a significant atmospheric loss rate of oxygen and nitrogen, which will make them uninhabitable within a few tens to hundreds of Myr, given a low replenishment rate from volcanism or cometary bombardment. Our non-thermal escape models have important implications for the habitability of the Proxima Centauri's terrestrial planet.